AUTIZM SPEKTRIDA BUZILISHI BOʻLGAN BOLALARNING PSIXOLOGIK XUSUSIYATLARI - Vapoyeva, R.R. (SCIENCE and SOCIETY, 2025)
The article lists psychological characteristics of children with autism spectrum disorders, their study by psychologists from abroad and Uzbekistan, analysis of clinical signs and socio-psychological characteristics and methodology determining the level of intelligence based on schemes and tables.
Keywords: autism; intelligence; nonverbal and verbal communication; anomalous; integration; attention; memory; speech; thinking; intuition; emotional-volitional sphere; aggression; mechanical memory; rehabilitation